Strategi Pengasuh Pondok Pesantren dalam Pengembangan Ekonomi Mandiri Santripreneur - Shofiyuddin, Moch; Zamroni, M Afif; Warti'ah; Maknuun, Lu' Lu' Il (Universitas KH. Abdul Chalim Pacet Mojokerto, 2023)
The article aims to find out and analyze the strategies of caregivers of Al Falah Islamic Boarding School, Pacet, Mojokerto, in developing entrepreneurial economic independence education for entrepreneurs. This article uses a qualitative approach with the type of case study research. Data was collected using observation, interviews and documentation. The analysis uses reduction, data encoding and verification. Checking the validity of the findings is done by extending observations and triangulation methods. The results of this article are 1) The Strategy of Islamic Boarding School Caregivers in Independent Economic Development for Santripren at Al-Falah Islamic Boarding School, Pacet, Mojokerto, using the following methods: a) Doctrination of students through a religious learning process, b) Adjustment of the field of expertise of students according to interests and talents by selection, c) Establish partnerships and cooperation with external parties, d) Incorporate independent economic entrepreneurship education in extracurricular activities of pesantren, e) Free education fees for students, f) Santri are required to have savings in Islamic boarding schools, g) Establish job training centres.